Peningkatan Hasil Belajar Pendidikan Agama Kristen Dan Budi Pekerti Siswa SD Negeri 173529 Tampahan Kabupaten Toba Melalui Ativasi Metode Scientific Approach - Selamat Jaya Sihite; Lince Sihombing; Damayanti Nababan; Andrianus Nababan; Maria Widiastuti (Pusat Riset dan Inovasi Nasional, 2023)
This study aims to determine whether the scientific approach method can improve the learning outcomes of PAK and Budi Pekerti of SDN 173529 Tampahan Kab. Toba positively and significantly. This research is quantitative research. The research population sample amounted to 14 people from class VI of SD Negeri 173529 Tampahan Kab. Toba (Non Probability Sampling). The results showed that the application of the Scientific Approach method succeeded in improving the learning outcomes of Christian Religious Education and Budi Pekerti Students of SD Negeri 173529 Tampahan Toba Regency. The increase in learning outcomes is known: 1) The percentage of classes that completed learning at meeting I was 71.43% with a sufficient category, 2) The percentage of classes that completed learning at meeting II was 85.71% with a high category, 3) The percentage of classes that completed learning at meeting III was 92.86% with a very high category.